Colonialism and Racism Reflected in Joseph Conrad's Heart of Darkness Novel (1902): A Post-colonial Perspective - Marfu'ah, Itsnaini Baroroh; , Dr. M. Thoyibi, M.S; , Mauly Halwat Hikmat, Ph. D (2014)
This paper displays colonialism and racism reflected in Joseph Conrad's Heart of Darkness. The study asking The study asking firstly what are the indicators of colonialism and racism. Secondly, how the colonialism and racism reflected in Heart of Darkness. Thirdly, why Joseph Conrad reveal the colonialism and racism in his novel. The object of this study is Heart of Darkness by Joseph Conrad. It uses Post-colonialism perspective. This study belongs to qualitative research. In this method there are two types of data source namely primary and secondary data source. The primary data source is the novel and the secondary data is other works or any information related to the study. Both data are collected through library research and analyzed by descriptive analysis. The result of the study is that: in the novel Joseph Conrad reflecting the practice of colonialism and racism in the nineteenth century. That the story of the novel is based on the Joseph Conrad's own experience.